Inequity in Mortality Rates and Potential Years of Life Lost Caused by Covid-19 in the Greater Santiago, Chile - Vargas-Rona, C; Elorrieta-Lopez, F; Maddaleno-Herrera, M; Villalobos-Dintrans, P; Ayala, A (Nature Research, 2023)
Several studies have shown that, in Chile, income inequality is relevant in explaining health inequities. The COVID-19 pandemic has also had a negative impact, with higher mortality rates in those municipalities of Greater Santiago with lower socioeconomic status. We study inequity in mortality based on Potential Years of Life Lost (PYLL) in 34 urban municipalities of the Metropolitan Region (Greater Santiago) and analyze its evolution between 2018 and 2021 and by COVID-19 waves. To compare the results obtained for PYLL, we also computed the mortality rates adjusted by direct standardization. In addition, we used the concentration index (CI) to measure the health inequalities between municipalities. In the first year of the pandemic, the absolute PYLL and the standardized mortality rate for all causes of death showed an increase of 13.6% and 18.9%, respectively. Moreover, 409,086 years of life were prematurely lost in 2020, one-fifth of them due to COVID-19. The concentration indices confirm inequality in both mortality rates and PYLL, where it is more pronounced when calculating the latter measure. Results show that the deaths due to the COVID-19 pandemic affected the most economically disadvantaged municipalities, and particularly young people in those places. © 2023, Springer Nature Limited.